(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1864)
Following James Farrer’s donation of artefacts from the 1862 excavation of the Know of Saverough (see ’Anniversary Meeting’, p9), this paper provides extracts from his account of the excavation. Several human skeletons were unearthed during this excavation and craniologist Dr Thurnam suggested that these remains may have belonged to pre-Scandinavian inhabitants of the Orkney islands. The author argues that there may have been two pre-Christian settlements at this site, one much earlier than the other. The remaining donations from the 12 January 1863 meeting are appended.